Analisis Kesulitan Belajar Kalkulus 1 Mahasiswa Teknik Informatika - Tatan Zaenal Mutakin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
This research aims to determine the factors that couse Information Technology Student difficulties in taking the course of Calculus 1. The method used was a survey with a sample of 160 research students. Data collection used was a questionnaire, questions that have been validated, and the score of final exams. All the said data were analyzed by using descriptive analysis, factor analysis, and multiple regressions. The results of the research are: 1) There are many factors that cause students difficulties in taking the course calculus 1; especially for students of Information Engineering University Indraprasta PGRI Jakarta. In addition there are two factors that cause students difficulties in attending in calculus 1, namely: both interest in learning and basic calculus skills are low. Of these two factors, the ability of the most dominant basic calculus that led to student learning outcomes calculus 1 low, 2) the results of factor analysis states that among the indicators that cause students difficulty in following the course calculus 1 are: (1) the student’s assumption that Calculus 1 has nothing to do with study of Information Engineering program, (2) less able to function in a reduction operation, (3) less capable of operating similar fractional rates, (4) less interest of calculus lesson 1, (5) less capable of normal operation of similar parts, (6) less capable in mixed fractional operations, (7) and less able to function in the addition operation.